Trend of Digital Literacy Skill Research in Communication Education Journals across Indonesia: from Research Design to Data Analysis - Nathanael, Garcia Krisnando (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
Empowerment of digital literacy skill intends to acquire. This study employed content analysis on 36 journal articles that had been published in SINTA (Science and Technology Index), an online scientific porta l managed by Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia, with articles published in 2017 – 2022 with digital literacy as the main focus of the study. This current study has revealed that over the past three years, there has been a significant increase in the number of publications focusing on research on digital literacy skill. The majority of the 36 publications the researcher reviewed showed that quantitative researches were one point or more superior to quantitative research. Additionally, senior high school students were primarily selected as the research subjects, with the topic of measuring the level of digital literacy skills being the most popular one. In light of the study’s findings, some recommendations have been made for additional research. First and foremost, it is essential to improve the research and development method in order to create more educational materials with the goal of raising teachers’ and students’ low levels of digital literacy. Second, it is advised that when conducting any research, the researchers choose the test that best fits their hypothesis and research design.